Study of Heavy Metal Content in Lola Snail (Trochus niloticus) in The Karang Island of Central Tapanuli Regency (Universitas Negeri Semarang, 2023)
Research on the analysis of heavy metal content in the waters of Karang Island, Central Tapanuli Regency aims to know the metal content in Lola Snail meat, sediment, and Lola Snail shells. The research method begins with taking samples of Lola snails and sediments on Karang Island and preparing the samples. Then, the samples were analyzed by AAS (Atomic Absorption Spectrometry) to determine the content of heavy metal elements in the meat of Lola Snail, followed by XRD (X-Ray Diffraction) testing to determine the content of heavy metal elements in sediments, and also testing with EDX (Energy Dispersive X-Ray) to determine the content of heavy metals in the shell. The results of the analysis on the AAS test showed that the order of heavy metal concentrations in Lola snail meat at station I was Zn Cr Cu Cd Pb, while at station II was Zn Cu Cr Cd Pb. The results of the sequence of heavy metal concentrations using XRD in sediments around Karang Island at the station I was Zn Cr Cu Cd Pb, while at station II was Zn Cd Cu Cr Pb. The results of the analysis on the shells of Lola snails using EDX at both stations showed they did not contain heavy metal elements (Pb, Cd, Cu, Cr, and Zn), but only contained O, Ca, Mg, Na, Al, and Si elements.